Influence of Body Mass Index on Inflammatory Profile at Admission in Critically Ill Septic Patients - Fernando G. Zampieri; Vanessa Jacob; Hermes V. Barbeiro; Fabiano Pinheiro da Silva; Heraldo P. de Souza (International Journal of Inflammation, 2015)
Introduction. Inflammation is ubiquitous during sepsis and may be influenced by body mass index (BMI). We sought to evaluate if BMI was associated with serum levels of several cytokines measured at intensive care unit admission due to sepsis. Methods. 33 septic patients were included. An array of thirty-two cytokines and chemokines was measured using Milliplex technology. We assessed the association between cytokine levels and BMI by generalized additive model that also included illness severity (measured by SAPS 3 score); one model was built for each cytokine measured. Results. We found that levels of epidermal growth factor, vascular endothelial growth factor, and interleukins 4, 5, and 13 were associated with BMI in a complex, nonlinear way, independently of illness severity. Higher BMI was associated with higher levels of anti-inflammatory interleukins. Conclusion. BMI may influence host response to infection during critical illness. Larger studies should confirm these findings.